Influence of different agricultural approvals on growing of post sucrose sunglass in conditions of Luhansk region - Маслійов, С. В.; Шевченко, А. М.; Степанов, В. В.; Бугайов, О. В. (Scientific Progress & Innovations, 2018)
Intermediate crops are primarily an important additional source of agricultural production. They allow crop rotation of intensive agriculture to significantly increase utilization rate of arable land (UR of AL), which characterizes the ratio of the area of crops to the total area of arable land. With the expansion of intermediate crops, the UR of AL increases from 1 to 1.3. Depending on the dates of sowing of the main crops, after harvesting of which intermediate crops are cultivated, they are divided into wintering, sowing and post-skeletal. Post-skeletal intermediate crops are sown after cutting the main winter crops and spring crops on green feed. The choice of post-ear crops is determined by specific soil-climatic conditions and household needs. In soil-climatic conditions in the north of Luhansk region with a thriving warm period of growth with sufficient moisture supply of plants, post-crop crops use corn, buckwheat, millet, soya, sunflower, and others. Our work revealed differences in the peculiarities of growing sunflower in post-crop sowing after winter rye, harvested on green mass. Experiments were conducted on experimental sites of Luhansk National University of Taras Shevchenko in 2015–2017. After harvesting of winter rye, an early-seeded hybrid of Pioneer P63LE113 sunflower was sown by rooting and surface treatment of the soil on herbicide (Treflan 4-5 l/ha, Harnes 2 kg/ha) and non-herbicide backgrounds. On both methods of sowing, insurance premiums were set at 20, 40 and 60 % to the optimal density of sunflower stand on ordinary crops of 70 th/ha, and broad-row – 50 th/ha. Flours of sunflower with harrow BZSS – 1.0, but on wide-range crop additional, if necessary, inter-row processing. The highest yields are provided when sown in a continuous manner and the maintenance of fields in a pure state of weeds. It eliminates inter-row processing.